Mining corruption, environmental damage, and the increasing unauthorized properties of state officials - Yustrisia, Lola; Wardiono, Kelik; Surbakti, Natangsa; Budiono, Arief (Edelweiss Applied Science and Technology, 2024)
Indonesia is blessed with natural resources in the form of minerals and coal. Their use must be directed towards the greatest welfare and prosperity of the people based on the 1945 Constitution. However, what is currently happening is the opposite. the Attorney General revealed case of alleged corruption in the trading system of tin commodities in the Bangka Belitung region. The suspects include businessmen, directors, crazy rich Indonesians, and artists who are now increasingly attracting public attention. The total state losses were equivalent to $16,667 billion USD. This research used a sociological legal research model. The research object was the legal behavior in the reality of society. It was found that to formulate appropriate law enforcement for mining corruption, Friedman’s legal system theory approach was used. This theory includes legal structures, with good synergy from each law enforcement institution. Concerning the legal substance, apart from using the Corruption Crime Law, perpetrators also need to be impoverished by regulating the crime of money laundering. In terms of legal culture, state officials should uphold ethics and integrity to achieve good governance. Meanwhile, restoration of environmental damage resulting from mining activities can begin with future environmental policies that are directed towards ensuring the safety and health of the human life as well as controlling the wise use of natural resources. The integration of environmental law and Islam can be carried out using a prophetic ethical approach. The prophetic paradigm interprets nature as something sacred as humans only borrow it and manage.